88 Lidocaine Incorporated Alprostadil-phentolamine Urethral Gel for Erectile Dysfunction: Patient Tolerability and Satisfaction. Issue 1 (1st April 2022) - Pham, R; Palasi, S; Blum, K; Howell, S; Beetz, J; Santarelli, S; Panuganti, S; Green, T; Wang, R
ABSTRACT: Introduction: Localized therapy remains an important tool in the armamentarium against ED in patients who decline surgical intervention. Options include intracavernosal injections (ICI) and intraurethral (IU) therapies. For patients averse to injections, IU can be an option. Discomfort is a common side effect of IU therapies. Objective: Herein, we assess the use, tolerability and satisfaction of a lidocaine incorporated IU gel treatment including phentolamine and alprostadil. Methods: In this single-center study, 75 patients were telephonically surveyed following the prescription of IU lidocaine-alprostadil-phentolamine gel for ED. Prior to IU therapy, all patients had ICI incorporated penile Doppler exams as part of their routine ED workup. Each survey consisted of 5 questions from the validated Sexual Health Inventory for Men (SHIM) questionnaire and 4 questions regarding satisfaction with IU therapy. Patients were excluded if they did not fill their IU prescription, did not answer after 3 attempted calls, declined participation, or were non-English speaking. Clinico-demographic factors were analyzed using chi-square, t-tests, and logistic regression to determine associations of treatment satisfaction. Results: Out of 75 patients, 39 had treatment data available for analysis. Median age of the cohort was 61 years (IQR 56-66). Hypertension and hyperlipidemia were the most common comorbidities within the group at 21 (53.8%) patients and 13 (33.3%) patients, respectively. Surveys were conducted a median 128 days after initial prescription. In total, 15 (38.4%) patients were satisfied with IU treatment. Thirty-seven (94.9%) patients did not report pain with IU gel usage. Prior success with <10 units of ICI alprostadil-papaverine-phentolamine (during penile Doppler or as a previous therapy) was associated with increased treatment satisfaction (p=0.039). Post-treatment SHIM scores were also associated with increased treatment satisfaction (p=0.047). Factors such as age, time since initial insult, hypertension, or hyperlipidemia were not found to influence treatment satisfaction. Conclusions: IU therapy is an acceptable alternative in patients interested in localized ED therapy who are averse to ICI. Patients who responded to <10 units of ICI was associated with IU treatment satisfaction. IU therapy has a success rate of ∼33%, with the most common adverse event being discomfort. In this study, lidocaine incorporated IU gel offered similar efficacy (38.4%) and is well-tolerated with 94.9% reporting no discomfort. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientic, Coloplast, Neotract